Mengatasi Masalah Keharmonisan Rumah Tangga Melalui Edukasi Seksualitas Pasca Persalinan - Amy Ratu Navisa; Sri Wahyuni; Tutik Rahayu (Journal of Medical Practice and Research, 2025)
The postpartum period represents a critical transitional phase that may significantly affect marital harmony due to physical, psychological, and sexual changes experienced by women after childbirth. Inadequate preparedness in addressing postpartum sexual changes often contributes to decreased communication quality and relational instability between spouses. This study aimed to analyze the effect of postpartum sexuality education on marital harmony among postpartum mothers. A quantitative experimental study with a pre-test–post-test control group design was conducted involving 128 postpartum mothers, divided equally into intervention and control groups. The intervention group received structured and interactive postpartum sexuality education, while the control group was provided with informational leaflets. Marital harmony was measured using a validated and reliable family harmony questionnaire. Data were analyzed using Wilcoxon and Mann–Whitney tests. The findings demonstrated a statistically significant improvement in marital harmony scores in the intervention group compared to the control group. These results indicate that postpartum sexuality education effectively enhances communication, emotional closeness, and adaptive coping within marital relationships. Integrating postpartum sexuality education into maternal health services is therefore essential to support relational stability and promote long-term family well-being after childbirth.